Quantifying the reduction in power variability of co-located offshore wind-wave farms. (February 2022) - Rasool, Safdar; Muttaqi, Kashem M.; Sutanto, Danny; Hemer, Mark
Abstract: Offshore wind energy and wave energy are two exploitable sources of renewable energy available in the same marine environment. A co-located energy harvesting system of these two resources has the potential to play a leading role in the recent renewable energy mix mandate. A co-located system of mature offshore wind technology and a nascent wave energy technology can exploit the synergies of the two technologies, including the reduced cost, the easy operation and maintenance, and more importantly the potential of decreased power variability. This paper deals with a multi-site analysis of wind and wave power resources, and the estimation of exploitable energy through different wind turbines and wave energy converters (WECs). Results are presented for NSW Australia, but the devised strategy is generic and can be implemented in any region. Ten WECs, with different operating principles, are used for the estimation of the exploitable wave power, and the best performing converter is considered for the co-located wind-wave farm. A power fluctuation factor is introduced to quantify the reduction in power variability of the co-located wind-wave farm. Different percentage mixes of wind and wave energy are evaluated for the co-located wind-wave farm in the multi-site analysis. Highlights: A multi-site analysis of wind and wave for estimation of exploitable energy. Performance evaluation of wind and wave energy conversion technologies. Power variability representation with power fluctuation factor for a co-located farm. Characterization of percentage share of wind and wave in a co-located farm.